Self-purifying capacity of the Carrizal River on effluents from the oxidation lagoon. Calceta. - Menéndez Vera, Jesús Yardhel (2022)
ABSTRACT. The objective of this research is to identify the self-purification capacity of the organic matter of the Carrizal River, factors that influence its quality, starting from the point of discharge of wastewater from the oxidation pond in the city of Calceta to the water purification plant "La Estancilla. Several monitoring and analyses were performed, such as flow, pH, temperature, dissolved oxygen and organic matter, using the Protocol for Monitoring Water Resources of Peru, taking 4 points before, during and after the discharge of domestic wastewater, with a sample at a white point as a reference, taken during the low water season of 2019 (September, October and November). For the definition of these points, an information survey of the study area was carried out with ArcGis v10.4.1 software using a georeferenced map with the sampling locations. Organic matter (BOD5) was analyzed in the environmental chemistry laboratories of the ESPAM "MFL" using a Martini pH 55 potentiometer and Milwaukee MI-605 oximeter (in situ). The data was then tabulated in Excel v14.0 software with the Streeter-Phelps model, projecting the self-purification of the Carrizal river by 23.76% of organic matter (BOD), from the point of mixing with the discharge up to 9000 meters, with a decrease from 7.28 mg/l to 5.52 mg/l.